Tools to evaluate pharmacokinetics data for establishing maximum residue limits for approved veterinary drugs: examples from JECFA's work. Issue 5 (May 2016) - Sanders, P.; Henri, J.; Laurentie, M.
Abstract : Maximum residue limits (MRLs) for residues of veterinary drugs are the maximum concentrations of residues permitted in or on a food by national or regional legislation. In the process of MRLs recommendations by the Joint FAO/WHO Expert Committee on Food Additives (JECFA), analysis of pharmacokinetic data describing the ADME process (absorption, distribution, metabolism and excretion) is a crucial step and requires the use of different pharmacokinetic tools. The results of animal metabolism studies are the prime determinants of the residue definition in food commodities. Substances labelled with radioactive isotopes are used so that the disposition of the residue can be followed as total residue and main metabolites concentrations. Residue depletion studies with radiolabelled parent drug will lead to the estimate of the time course of the total residue and to determine a marker residue. Depletion studies with an unlabelled drug provide more information on the time course of the marker residue in raw commodities after administration under approved practical conditions of use. By use of this information and after conversion with the total/residue marker ratio, MRLs are derived by comparison of the acceptable daily intake with the daily intakes calculated with different scenarios of dietary exposure. Progress in pharmacokinetic model such as physiologically based pharmacokinetics and population pharmacokinetics will drive the future research in this field to improved veterinary drug development. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Establishment of maximum residue limits for veterinary drugs requires studying the absorption, distribution, metabolism and excretion through different kinds of studies. The paper summarizes the process illustrated by the study of monepantel in sheep.